Health Practice Professionals as the Foundation of the Saudi Healthcare System: Workforce Integration and System Transformation under Vision 2030 (The Review of Diabetic Studies, 2025)
The healthcare system in Saudi Arabia is undergoing a comprehensive transformation, driven by demographic change, the epidemiological transition, and the key goals of national development initiatives. Fundamental to this reform is a diverse, multidisciplinary health workforce comprising clinical practitioners, allied health professionals, public health specialists, healthcare administrators, and technical support personnel. This overview assesses the integrated roles of health practice professionals within the Saudi healthcare system, emphasizing cross-disciplinary cooperation, workforce development, professional accountability, and system sustainability. By adopting a health systems perspective, the article highlights how strengthening and valuing all health practice roles is essential to achieving high-quality, equitable, and high-performing healthcare in accordance with national reform priorities.